Primary therapy and relative survival in patients with lymphoplasmacytic lymphoma/Waldenström macroglobulinaemia: a population‐based study in the Netherlands, 1989–2018. (3rd October 2021) - Amaador, Karima; Kersten, Marie José; Visser, Otto; Brink, Mirian; Posthuma, Eduardus F. M.; Minnema, Monique C.; Vos, Josephine M. I.; Dinmohamed, Avinash G.
Summary: It is unclear how treatment advances impacted the population‐level survival of patients with lymphoplasmacytic lymphoma/Waldenström macroglobulinaemia (LPL/WM). Therefore, we assessed trends in first‐line therapy and relative survival (RS) among patients with LPL/WM diagnosed in the Netherlands between 1989 and 2018 ( N = 6232; median age, 70 years; 61% males) using data from the nationwide Netherlands Cancer Registry. Patients were grouped into three age groups (<65, 66–75 and >75 years) and four calendar periods. Overall, treatment with anti‐neoplastic agents within 1 year post‐diagnosis gradually decreased over time, following a broader application of an initial watch‐and‐wait approach. Approximately 40% of patients received anti‐neoplastic therapy during 2011–2018. Furthermore, use of chemotherapy alone decreased over time, following an increased application of chemoimmunotherapy. Detailed data among 1596 patients diagnosed during 2014–2018 revealed that dexamethasone‐rituximab‐cyclophosphamide was the most frequently applied regimen; its use increased from 14% to 39% between 2014 and 2018. The 5‐year RS increased significantly over time, particularly since the introduction of rituximab in the early–mid 2000s. The 5‐year RS during 1989–1995 was 75%, 65%, and 46% across the age groups compared to 93%, 85%, and 79% during 2011–2018. However, the survival improvement was less pronounced after 2011. Collectively, the impressive survival improvement may be accounted for by broader application of rituximab‐containing therapy. The lack of survival improvement in the post‐rituximab era warrants studies across multiple lines of therapy to further improve survival in LPL/WM.